The Role of Oxidative Stress in the Pathophysiology and Progression of Type 2 Diabetes Mellitus: Molecular Mechanisms and Therapeutic Perspectives: A Narrative Review - Lamyaa Kadhim Ouda (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Type 2 diabetes mellitus is a complex metabolic disorder characterized by chronic hyperglycemia, insulin resistance, and progressive β-cell dysfunction, with increasing global prevalence and associated complications. Specific Background: Oxidative stress, defined as an imbalance between reactive oxygen species production and antioxidant defenses, has been increasingly recognized as a central factor in metabolic dysregulation and disease progression. Knowledge Gap: Despite extensive research, uncertainties remain regarding the precise molecular pathways linking oxidative imbalance to insulin resistance, β-cell dysfunction, and diabetic complications, as well as the translational value of antioxidant-based therapies. Aims: This narrative review aims to synthesize current evidence on the role of oxidative stress in the pathophysiology of type 2 diabetes mellitus and to elucidate key molecular mechanisms and therapeutic approaches. Results: Findings indicate that chronic hyperglycemia promotes excessive reactive oxygen species generation through mitochondrial dysfunction, polyol and hexosamine pathways, advanced glycation end-products formation, and endoplasmic reticulum stress, leading to impaired insulin signaling, β-cell apoptosis, inflammation, and vascular complications. Novelty: The study integrates molecular, cellular, and clinical perspectives into a comprehensive framework linking oxidative stress with metabolic dysfunction and disease progression. Implications: Improved understanding of oxidative stress mechanisms may support the development of targeted therapeutic strategies, including antioxidant interventions and lifestyle modifications, for better management and prevention of type 2 diabetes mellitus. Highlights: • Chronic Hyperglycemia Drives Reactive Oxygen Species Through Multiple Biochemical Pathways• Mitochondrial Dysfunction and Endoplasmic Reticulum Stress Contribute to Metabolic Imbalance• Therapeutic Approaches Include Antioxidants, Pharmacological Agents, and Lifestyle Strategies Keywords: Type 2 Diabetes Mellitus, Oxidative Stress, Reactive Oxygen Species, Insulin Resistance, Antioxidant Therapy.